DREDGING, MUD, AND DUNNING-KRUGER: Dragagem, lama e Dunning-Kruger - Augusto França Schettini, Carlos (Arquivos de Ciências do Mar, 2022)
The human being has a cognitive pattern of always considering the work of others simple, and this is known as the Dunning-Kruger effect. All areas of knowledge present complexities that are only understood by those who are dedicated to going deeper into a particular topic. This manuscript talks (superficially) about mud and dredging, which is a contemporary and very relevant topic for economic development and the preservation of the environment. In short, dredging is taking sediment from one place and putting it in another. Simple! However, when this sediment is mud, there are several aspects inherent to this type of material that make the evaluation of its behavior somewhat complex, synergistically with the complexity of coastal hydrodynamics. Keywords: cohesive sediment, hydrodynamics, flocculations, fluid mud.